Design of a variable stiffness actuator based on a multi-pulley system with a spring - To, Dong Anh Khoa; Chau, Hoang Phuc; Nguyen, Vu Linh (Vietnam Journal of Mechanics, 2024)
This paper presents a variable stiffness actuator (VSA) based on a multi-pulley system with a linear spring. In this design, twelve pairs of outer pulleys and six pairs of inner pulleys are evenly arranged around a center and are serially connected to a spring through a cable. When the inner pulleys rotate about the center point, the spring is extended to generate an elastic force exerted on the cable and then transmitted to the output link as an output torque, resulting in an output stiffness. The significance of the proposed design is that it can quickly vary the output stiffness by adjusting the positions of the inner pulleys using a cam disk. Also, all the components are adequately arranged, making the design compact. In this work, the design concept, analysis, and a numerical example are provided to illustrate the proposed VSA and its performance. It is shown that the VSA can offer a maximum output torque of 30 N-cm with a maximum deflection of 40 degrees. These parameters can demonstrate the wide application and high adaptability of the proposed actuator to various environments.